KRITIK SOSIAL DALAM KUMPULAN CERPEN LUDAH NABI DI LIDAH SYEKH RABA KARYA ROYYAN JULIAN (SEBUAH PENDEKATAN SOSIOLOGI SASTRA) - Abdurrahman, Abdurrahman (Universitas Madura, 2022)
This research is intended to describe and reveal social criticism in the collection of short stories Lidah Nabi Di Lidah Syekh Raba. While the object of this research is the social criticism contained in the short story. The method used in this research is qualitative method. The approach used in this study is the sociology of literature approach. The description of social criticism contained in the short story Lidah Nabi Di Lidah Syekh Raba. which contains (1) criticism in the field of environment which reveals about (a) respect for nature. (b) moral responsibility towards nature (2) Criticism in the field of Politics which contains about (a) Power over the government. (b) criticism of the regulations in government. (3) Criticism in the field of religion includes (a) complete belief in God. (b) surrender to God